2022
DOI: 10.1371/journal.pone.0274753
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nanomaterials synthesized from Spirulina platensis extract and their potential antifungal activity

Abstract: Nowadays, fungal infections increase, and the demand of novel antifungal agents is constantly rising. In the present study, silver, titanium dioxide, cobalt (II) hydroxide and cobalt (II,III) oxide nanomaterials have been synthesized from Spirulina platensis extract. The synthesis mechanism has been studied using GCMS and FTIR thus confirming the involvement of secondary metabolites, mainly amines. The obtained products have been analysed using XRD, SEM, TGA and zeta potential techniques. The findings revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 73 publications
(72 reference statements)
1
16
0
Order By: Relevance
“…TiO 2 -NPs possess tremendous surface catalytic potential; 41,42 however, green synthesized, homogeneous and small sized TiO 2 -NPs have been scarcely reported in the literature. 43,44 Recently, anatase-TiO 2 quantum dots with a crystallite size of 4.2 nm were obtained by chemical synthesis in a time-consuming and complex procedure utilizing acetylacetone, n -butanol, and 4-dodecylbenzene sulfonic acid. 28 In the current study, TiO 2 -NPs with a small crystallite size (∼4 nm) and a homogeneous morphology seem to result from the synergistic effect of secondary metabolites from olive leaves, reaction temperature, and optimized pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 -NPs possess tremendous surface catalytic potential; 41,42 however, green synthesized, homogeneous and small sized TiO 2 -NPs have been scarcely reported in the literature. 43,44 Recently, anatase-TiO 2 quantum dots with a crystallite size of 4.2 nm were obtained by chemical synthesis in a time-consuming and complex procedure utilizing acetylacetone, n -butanol, and 4-dodecylbenzene sulfonic acid. 28 In the current study, TiO 2 -NPs with a small crystallite size (∼4 nm) and a homogeneous morphology seem to result from the synergistic effect of secondary metabolites from olive leaves, reaction temperature, and optimized pH.…”
Section: Resultsmentioning
confidence: 99%
“…The observed lattice planes are attributed to the (101) planes of anatase. TiO 2 -NPs possess tremendous surface catalytic potential 41,42 ; however, green synthesized, homogenous and small sized TiO 2 -NPs were scarcely reported in the literature 43,44 . Recently, anatase-TiO 2 quantum dots with a crystallite size of 4.2 nm were obtained by chemical synthesis in a time-consuming and complex procedure utilizing acetylacetone, n-butanol, and 4dodecylbenzene sulfonic acid 28 .…”
Section: Catalysis Science and Technology Accepted Manuscriptmentioning
confidence: 99%
“…On the other hand, the NPs cause DNA damage, block ATP synthesis, and modify the fatty acids and cellular structure. 96 Abbas et al, 2021 97 reported the antifungal activity of extracellular SeNPs against yeast fungi (C. Albicans ATCC1023). AgNPs, titanium dioxide, hydroxide, and cobalt(II, III) oxide biosynthesized using S. platensis were extracted with strong antifungal activity.…”
Section: Biomedicalmentioning
confidence: 99%
“…With the rapid developments in nanoscience and its application in the medicine field, researchers’ interest, encouraging them to investigate the use of nanotechnology in the health sector and thus nanomedicine, has emerged. , In this context, various nanoparticles have been used for their antibacterial activities. There are numerous reports for antibacterial activity of zinc, gold, and silver nanoparticles, among which silver nanoparticles (AgNPs) have been extensively explored due to their high antibacterial activity. The antibacterial activity of silver nanoparticles can be attributed to various mechanisms such as disruption of the cell wall and cytoplasmic membrane, denaturation of ribosomes, interruption of adenosine triphosphate (ATP) production, membrane disruption by reactive oxygen species, and interference of deoxyribonucleic acid (DNA) replication. It has already been identified that there is an increased antibacterial activity of Ag at the nanoscale which has further found applications in the healthcare sector. However, its activity against drug resistant microbes has been challenging . Moreover, to reduce the toxicity of these nanoparticles, modification of the surface of these AgNPs with materials such as biomolecules, including peptides, plant extract, polymers, such as poly­( l -lysine), and carboxymethyl cellulose has been carried out using either covalent or physical interactions. …”
Section: Introductionmentioning
confidence: 99%